2001
DOI: 10.1095/biolreprod65.2.622
|View full text |Cite
|
Sign up to set email alerts
|

2-Methoxyestradiol, an Endogenous Estradiol Metabolite, Differentially Inhibits Granulosa and Endothelial Cell Mitosis: A Potential Follicular Antiangiogenic Regulator1

Abstract: 2-Methoxyestradiol (2-ME) is an estradiol metabolite with antiangiogenic and antitumor activity. It is formed by granulosa cell (GC) catechol-O-methyltransferase activity and is present in the normal follicle at high concentrations. In this unique microenvironment, it may regulate selected cell types via autocrine and/or paracrine action. To assess the possibility that 2-ME or estradiol might exert differential mitotic and/or apoptotic effects on endothelial cells and GCs, we compared their actions on primary … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
21
0
1

Year Published

2005
2005
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(23 citation statements)
references
References 43 publications
1
21
0
1
Order By: Relevance
“…In addition to pro-angiogenic molecules, negative regulators of angiogenesis were observed (Tempel et al 2000, Shang et al 2001, Grasselli et al 2003. The present work demonstrates that factors contained in follicular fluid regulate the transcription of angiogenesis-modulating genes in endothelial cells and thus could help to explain the temporal and spatial discrepancy between the high expression of VEGF and the restricted angiogenesis in the preovulatory follicle.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to pro-angiogenic molecules, negative regulators of angiogenesis were observed (Tempel et al 2000, Shang et al 2001, Grasselli et al 2003. The present work demonstrates that factors contained in follicular fluid regulate the transcription of angiogenesis-modulating genes in endothelial cells and thus could help to explain the temporal and spatial discrepancy between the high expression of VEGF and the restricted angiogenesis in the preovulatory follicle.…”
Section: Discussionmentioning
confidence: 99%
“…Experimental evidence suggests that granulosa cells are also the source of angiogenesis inhibitors, such as hyaluronic acid (Tempel et al 2000) and 2-methoxyestradiol (Shang et al 2001). However, detailed studies investigating the cascade of events controlling angiogenesis during folliculogenesis and corpus luteum formation in the human have not been reported.…”
Section: Introductionmentioning
confidence: 99%
“…One such compound is 2-methoxyestradiol, a natural metabolite of estradiol, which has demonstrated, in in vitro and in vivo models, anti-angiogenic and anti-proliferative activity [11][12][13][14][15][16]. However, phase I clinical trials for 2-MeOE2, dosed at 1600-3000 mg/day, have been terminated early due to extremely low drug plasma bioavailability [17].…”
Section: Introductionmentioning
confidence: 99%
“…Several reports have shown a strong inhibitory effect of 2-methoxyestradiol (2-ME 2 ), which is synthesized in the ovarian follicles and present in the follicular fluid, on granulosa cell proliferation in different assays (12)(13)(14). Shang et al (12) demonstrated an additional strong antiangiogenic impact of 2-ME 2 on ovarian angiogenesis, adding another facet to mediate the antifollicular effect of this compound.…”
mentioning
confidence: 99%